Studies in Health Technology and Informatics Volume 22 - Healthcare Card Systems EUROCARDS Concerted Action - Doare, H. (IOS Press, 2014)
working groups in the context of the Eurocards Concerted Action. The Eurocards Concerted Action is an Advanced Informatics in Medicine (MM) Concerted Action on Patient Data Cards created in late 1993 and due to report early in 1995. An extension of Eurocards including two new working groups has been agreed upon to take into account the cooperation between the E.U. and Canada. All of these documents have been consolidated and validated during a workshop gathering 25 experts from 11 countries.